Collagen Membrane And Leukocyte Platelet Rich Fibrin For Periodontal Regeneration In An In-frabony Defect: A Case Report (Journal of Pharmaceutical Negative Results, 2023)
Aim: To demonstrate a case with clinical and functional improvement of a molar with advanced mobility following the application of Leukocyte- rich Platelet Rich Fibrin in an infrabony defect and coverage with collagen membrane.Methods: A 26 years old female presenting with masticatory problem associated with edentulous areas and mobility in some of the remaining dentition. The case was diagnosed as generalized Periodontitis Stage IV Grade C, the surgical phase comprised open flap debridement of the maxillary second premolar as well as simultaneous application of L-PRF within an infrabony defect affecting the adjacent first molar. Collagen membrane was used to cover the L-PRF before wound closure. The patient was enrolled in a meticulous supportive care during the study period of 6 months.Results: Baseline data revealed a grade III mobility with a 5 mm clinical attachment level (CAL) that is associated with a pocket probing depth (PPD) of 6 mm, clinical bone defect depth of 7 mm on the mesial surface of the tooth, and radiographic base of defect depth (BD) of 7.9 mm. At 6 months following surgery, recorded parameters for the CAL, PPD were 4, and 2 mm respectively. The mobility regressed to grade I and the radiographic BD lessened to 6.7 mm.Conclusion: The presented case demonstrated the promising outcomes of using collagen membranes with L-PRF in the treatment of infrabony pockets with advanced periodontal loss in stage IV grade C periodontitis.